Protective Effect of Acacia nilotica (L.) against Acetaminophen-Induced Hepatocellular Damage in Wistar Rats - Narayanan Kannan; Kunnathur Murugesan Sakthivel; Chandrasekaran Guruvayoorappan (Advances in Pharmacological Sciences)
The potential biological functions of A. nilotica have long been described in traditional system of medicine. However, the protective effect of A. nilotica on acetaminophen-induced hepatotoxicity is still unknown. The present study attempted to investigate the protective effect of A. nilotica against acetaminophen-induced hepatic damage in Wistar rats. The biochemical liver functional tests Alanine transaminase (ALT), Aspartate transaminase (AST), Alkaline phosphatase (ALP), total bilirubin, total protein, oxidative stress test (Lipid peroxidation), antioxidant parameter glutathione (GSH), and histopathological changes were examined. Our results show that the pretreatment with A. nilotica (250 mg/kg·bw) orally revealed attenuation of serum activities of ALT, AST, ALP, liver weight, and total bilirubin levels that were enhanced by administration of acetaminophen. Further, pretreatment with extract elevated the total protein and GSH level and decreased the level of LPO. Histopathological analysis confirmed the alleviation of liver damage and reduced lesions caused by acetaminophen. The present study undoubtedly provides a proof that hepatoprotective action of A. nilotica extract may rely on its effect on reducing the oxidative stress in acetaminophen-induced hepatic damage in rat model.